CORPORATE GOVERNANCE, RISK MANAGEMENT, AND BUSINESS ETHICS ON FIRM PERFORMANCE IN THE MODERN BUSINESS ENVIRONMENT - Ramiyati, Nekky; Putra, Firdaus; Widiarta, I Putu Gede Didik; Sofalina, Fresa Dwi Juniar (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study examines the impact of corporate governance, risk management, and business ethics on firm performance in the modern business environment. Using a quantitative research approach, data were collected from publicly listed firms and analyzed using multiple regression techniques. The findings indicate that corporate governance, risk management, and business ethics significantly and positively influence firm performance. Strong governance structures enhance decision-making, transparency, and accountability, leading to improved financial outcomes. Effective risk management strategies help firms navigate uncertainties, reducing financial and operational risks. Ethical business practices contribute to long-term sustainability by fostering stakeholder trust and corporate reputation. These results support the resource-based view and stakeholder theory, emphasizing the strategic importance of governance, risk management, and ethical conduct in achieving competitive advantage. The study provides theoretical and practical implications for businesses, policymakers, and investors, highlighting the necessity of robust governance frameworks, proactive risk management, and corporate ethics in enhancing firm performance. Future research should explore industry-specific effects and incorporate longitudinal analyses to assess the long-term impact of these factors on business success.